Evolutionary Game and Simulation in Forest Rights Exchange Based on the Supplier-Demander View - Lin, Junjie; Zhang, Qun; Wei, Yuanzhu (Mathematical problems in engineering, 2022)
At present, the forest rights exchange market in China is in its early stages. Forest rights exchange faces low circulation problems. The strategic choices of supply and demand play an important role in enhancing the efficiency of forest rights exchange. However, only limited empirical evidence has been provided on the strategic selection of forest rights exchange from the perspective of the dynamic game. Based on field investigation, this study constructed a dynamic game model and explored the dynamic evolution process of different strategic behaviors based on evolutionary game theory. Furthermore, a numerical simulation was conducted to evaluate the rationality of the theoretical model. The results show that several factors affected the strategies of transaction subjects including transaction price, transaction cost, forestry revenue, and nonforestry revenue. These factors are important means to regulating the forest rights exchange. In terms of policy implications, we suggest that diversity measures should also be considered to formulate policies of transaction price management and to encourage forestland owners to exchange forestland with enterprises and cooperatives. Moreover, additional efforts are needed to establish and improve the forest rights exchange market.